A Critical Analysis of the Influence of Perception on Compliance Behavior of Income Zakat - HAJI-OTHMAN, YUSUF; YUSUFF, MOHD SHOLEH SHEH; CHEUMAR, MOHAMMADTAHIR (The journal of contemporary issues in business and government, 2021)
Kedah issued a religious decree making it compulsory to pay income zakat in 1997. However, the collection of income zakat amongst Muslims who have fulfilled the conditions to pay income zakat in Kedah has remained low. Some public educators in Kedah did not pay income zakat to Kedah State Zakat Board because of the perception that they could pay zakat at other zakat institution. Also, they showed a lack of confidence in the Kedah State Zakat Board's ability to manage and distribute zakat. Studies on zakat compliance have shown mixed and inconclusive evidence regarding the determinants of income zakat compliance. Therefore, this study critically analyses the influence of perception towards equity in zakat distribution, perception towards the facility, perception towards law, and perception towards service quality on compliance behavior of income zakat in Kedah, Malaysia. This study employs a quantitative approach where primary data is collected using a questionnaire instrument; data is analyzed using PLS-SEM to determine significant determinants of compliance behavior of income zakat. This study provides empirical evidence that perception towards facility and service quality has significant relationships with income zakat's compliance behavior. However, perception towards equity in zakat distribution and perception towards law are not significant determinants of compliance behavior of income zakat in Kedah. This study is hoped to provide evidence that could be used as guidance for suitable policy and measures by Kedah State Zakat Board to improve zakat collection in the future.